PENGEMBANGAN LKPD BERBASIS PROJECT BASED LEARNING (PjBL) PADA MATERI SEGIEMPAT DAN SEGITIGA DI KELAS VII SMP - Nelia Safenita; Lucky Jufri; Alfi Yunita (Jurnal Karya Pendidikan Matematika, 2023)
This type of research is development research using R&D (Research and Development) with the Plomp development model consisting of three stages, namely Preliminary research, prototyping phase, assessment phase but in this study it only reached the prototyping phase. The instruments used are validity, practicality and independence questionnaires. The result of the validity of the validator is 88.57% with very valid criteria. The results of the practicality of learning worksheets with one mathematics teacher and students obtained a score of 97.4% in the very practical category. The learning outcomes of students using LKPD 6 students obtained a value of 93.40% with very valid criteria. Based on the results of this study, it can be concluded that learning media using Project Based Learning (PjBL) Based Learning Worksheets on Quadrilaterals and Triangles Material are valid and practical, and Project Based Learning (PjBL) Based Worksheets make students independent in the learning process on quadrilaterals and triangles material .